(untitled) (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2006)
Is there a significant difference between Plato’s texts and what is known as ‘Platonism’, that is, the philosophical tradition that claims Plato as its progenitor? Focusing on the Symposium, an attempt is made here to show that, far from merely fitting neatly into the categories of Platonism – with its neat distinction between the super-sensible and the sensible – Plato’s own text is a complex, tension-filled terrain of countervailing forces. In the Symposium this tension pertains between the perceptive insights, on the one hand, into the nature of love and beauty, as well as the bond between them, and the metaphysical leap, on the other hand, from the experiential world to a supposedly accessible, but by definition super-sensible, experience-transcending realm. It is argued that, instead of being content with the philosophical illumination of the ambivalent human condition – something consummately achieved by mytho-poetic and quasiphenomenological means – Plato turns to a putatively attainable, transcendent source of metaphysical reassurance which, moreover, displays all the trappings of an ideological construct. This is demonstrated by mapping Plato’s lover’s vision of ‘absolute beauty’ on to what Jacques Lacan has characterized as the unconscious structural quasi-condition of all religious and ideological illusion.